THE ROLE OF SELF-CONFIDENCE IN MEDIATING THE EFFECT OF WORK DISCIPLINE AND REWARD TO EMPLOYEE PERFORMANCE IN PRIVATE COMPANIES IN SERANG DISTRICT - Juwita Sari; Tata Rustandi; Udin Suadma (Lingua: Jurnal Bahasa, Sastra dan Pengajarannya)
ABSTRACT